Genetic polymorphisms of DAT1 and COMT differentially associate with actigraphy-derived sleep–wake cycles in young adults. (June 2014) - Valomon, Amandine; Holst, Sebastian C.; Bachmann, Valérie; Viola, Antoine U.; Schmidt, Christina; Zürcher, Jurian; Berger, Wolfgang; Cajochen, Christian; Landolt, Hans-Peter
<x xml:space="preserve">Abstract</x> Accumulating evidence suggests that dopamine plays a key role in sleep–wake regulation. Cerebral dopamine levels are regulated primarily by the dopamine transporter (DAT) in the striatum and by catechol-O-methyl-transferase (COMT) in the prefrontal cortex. We hypothesized that the variable-number-tandem-repeat (VNTR) polymorphism in the 3′-untranslated region of the gene encoding DAT (DAT1, SLC6A3; rs28363170) and the Val158Met polymorphism of COMT (rs4680) differently affect actigraphy-derived rest-activity cycles and sleep estimates in healthy adults (65 men; 45 women; age range: 19–35 years). Daytime sleepiness, continuous rest-actigraphy and sleep diary data during roughly 4-weeks were analyzed. Nine-repeat (9R) allele carriers of DAT1 (n = 48) more often reported elevated sleepiness (Epworth sleepiness score ≥10) than 10-repeat (10R) allele homozygotes (n = 62, p < 0.02). Moreover, male 9R allele carriers showed higher wrist activity, whereas this difference was not present in women ("DAT1 genotype" × "gender" interaction: p < 0.005). Rest-activity patterns did not differ among COMT genotypes. Nevertheless, a significant "COMT genotype" × "type of day" (workdays vs. rest days) interaction for sleep duration was observed (p = 0.04). The Val/Val (n = 36) and Met/Met (n = 24) homozygotes habitually prolonged sleep on rest days compared to workdays by more than 30 min, while Val/Met heterozygotes (n = 50) did not significantly extend their sleep (mean difference: 7 min). Moreover, whereas the proportion of women among the genotype groups did not differ, COMT genotype affected body-mass-index (BMI), such that Val/Met individuals had lower BMI than the homozygous genotypes (p < 0.04). While awaiting independent replication and confirmation, our data support an association of genetically-determined differences in cerebral dopaminergic neurotransmission with daytime sleepiness and individual rest-activity profiles, as well as other sleep-associated health characteristics such as the regulation of BMI. The differential associations of DAT1 and COMT polymorphisms may reflect the distinct local expression of the encoded proteins in the brain.